2005
DOI: 10.1089/jmf.2005.8.86
|View full text |Cite
|
Sign up to set email alerts
|

Du-zhong (Eucommia ulmoidesOliv.) Cortex Water Extract Alters Heme Biosynthesis and Erythrocyte Antioxidant Defense System in Lead-Administered Rats

Abstract: This study examined the ameliorative effect of a Du-zhong (Eucommia ulmoides Oliv.) cortex water extract (DzCw) on heme biosynthesis and erythrocyte antioxidant enzyme activities in lead (Pb)-administered rats. Male rats were divided into three groups: normal control group, Pb control group (Pb), and DzCw-administered Pb group (Pb + DzCw). The Pb (25 mg/kg of body weight) was administered orally once a week for 4 weeks, while the DzCw was administered orally at a dosage of 0.139 g of DzCw/kg of body weight/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…(EUE), is one of the traditional tonic medicines of Korea, China, and Japan. As a folk medicine, EUE is used to fortify the muscles and lungs, lower blood pressure, prevent miscarriage, improve the tone of liver and kidneys, and promote longevity (Jiang et al, 2011;Lee et al, 2005;Luo et al, 2010;Kwan et al, 2003). Moreover, the aqueous extract of EUE, commonly known as Du-zhong tea, is a popular folk drink in Japan, is through to be a functional health food (Nakajawa, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…(EUE), is one of the traditional tonic medicines of Korea, China, and Japan. As a folk medicine, EUE is used to fortify the muscles and lungs, lower blood pressure, prevent miscarriage, improve the tone of liver and kidneys, and promote longevity (Jiang et al, 2011;Lee et al, 2005;Luo et al, 2010;Kwan et al, 2003). Moreover, the aqueous extract of EUE, commonly known as Du-zhong tea, is a popular folk drink in Japan, is through to be a functional health food (Nakajawa, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…EuO extracts have antihypertensive, antioxidative, and antigastric ulcer effects (Metori et al, 1997;Deyama et al, 2001;Yang et al, 2003). Water extracts of EuO leaves have been reported to have potent antimutagenic effects (Nakamura et al, 1997;Lee et al, 2005;Luo et al, 2009). EuO extracts have also been reported to enhance collagen synthesis (Metori et al, 1997;Li et al, 2000a;2000b;Deyama et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…27) Taking these findings together, it is suggested that oxidative stress, which is induced by lead, is recovered by natural antioxidants, such as ascorbic acid, 28) epigallocatechin-3-gallate 29) and plant extracts etc. 30,31) Marine algae have the potential to improve the biochemical imbalances induced by various toxins associated with free radicals. The unicellular green algae Chlorella vulgaris (CV) contains many bioactive substances with medicinal properties.…”
Section: Introductionmentioning
confidence: 99%